Aquaculture governance: five engagement arenas for sustainability transformation - Partelow, Stefan; Asif, Furqan; Troell, Max; Stoll, Joshua; Stentiford, Grant D.; Salayo, Nerissa D.; Pin, Nie; Paramita, Adiska O.; Mizuta, Darien D.; Marschke, Melissa J.; Little, David C.; Kühnhold, Holger; et al. (Elsevier, 2023)
A greater focus on governance is needed to facilitate effective and substantive progress toward sustainability transformations in the aquaculture sector. Concerted governance efforts can help move the sector beyond fragmented technical questions associated with intensification and expansion, social and environmental impacts, and toward system-based approaches that address interconnected sustainability issues. Through a review and expert-elicitation process, we identify five engagement arenas to advance a governance agenda for aquaculture sustainability transformation: (1) setting sustainability transformation goals, (2) cross-sectoral linkages, (3) land–water–sea connectivity, (4) knowledge and innovation, and (5) value chains. We then outline the roles different actors and modes of governance can play in fostering sustainability transformations, and discuss action items for researchers, practitioners, and policymakers to operationalize activities within their engagement arenas.